Research progress on the kynurenine pathway in the prevention and treatment of Parkinson's disease - Ping Chen; Xiaofei Geng (Taylor & Francis Group, 2023)
Parkinson's disease (PD) is characterised by progressive death of dopamine (DA) neurons in the substantia nigra pars compacta (SNpc) and pathological accumulation of α-synuclein fibrils, as well as central nervous system inflammation. Elevated levels of central inflammatory factors in PD disrupt the kynurenine pathway (KP) and favour the activation of excitotoxic branches, leading to a significant reduction in the neuroprotective metabolite kynurenic acid (KYNA) and a significant increase in the neurotoxic metabolite quinolinic acid (QUIN), which exacerbates excitotoxicity and amplifies the inflammatory response, closely related to the occurrence and development of PD. KYNA analogs, precursor drugs, and KP enzyme modulators may represent a new therapeutic strategy for PD. This article reviews the role of KP in the neurodegenerative pathology of PD and its prevention and treatment, aiming to provide necessary theoretical basis and new ideas for the study of the neurobiological mechanisms underlying PD-related behavioural dysfunction and targeted interventions.